Isolasi and Identification of Bacteria from the Urine Fluid Organic Fertilizer (POC)Ettawa Crossbred (PE) in The Sleman Regency - Widodo Suwito; A.E.T.H. Wahyuni; Widagdo Sri Nugroho; Bambang Sumiarto; Utomo Bimo Bekti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
Urine is a by product from Ettawa crossbred (PE) goat farm in Sleman regency. In addition, the manure urine goats can be used for fluid organic fertilizer (POC). Recently, organic farming is more interesting for people because it does not use any chemical fertilizers. Salmonella sp and E. coli O157:H7 are pathogenic bacteria that can contaminate agricultural products and dangerous for public health. One of sources of contamination in agricultural products is due to the organic fertilizer. Therefore, the aim of the present study was to determine pathogenic bacteria from POC urine PE goats in Sleman regency. A total of 8 POC samples were collected from PE goat urine in Sleman regency. These samples were analyzed for Salmonella sp, E. coli O157:H7 and other pathogenic bacteria by using biochemical reactions. All samples are negative for Salmonella sp. and E. coli O157:H7 as well. Whereas, 85% of 8 samples are positive for Pseudomonas sp. The present study showed that POC from PE goats farm in Sleman regency are negative for pathogenic bacteria.